The bottom of the harbor - Mitchell, Joseph 1908-1996 (Pantheon Books, 2008)
On the centennial of Mitchell's birth comes this new edition of the classic collection containing his most celebrated pieces about New York City
"Originally published in slightly different form by Little, Brown in 1959"
Keywords: Harbors / New York (State) / New York; Waterfronts / New York (State) / New York; Alltag, Brauchtum; Englisch; Erzählung; Literatur; New York (N.Y.) / Social life and customs; Hafen New York- Manhattan -- New York, NY; USA; Anthologie